Pengaruh Variasi Pendinginan Terhadap Kekasaran Permukaan Hasil Proses Milling Pada Material Stainless Steel AISI 304 - Unggul Satria Jati; Dian Prabowo; Hety Dwi Hastuti (Infotekmesin, 2024)
Machining processes in current developments are required to be more environmentally friendly, the use of coolant has a big impact on the environment. So air cooling media is an alternative that can be used to reduce production costs and implement environmentally friendly machining processes. This research aims to determine the level of surface roughness on AISI 304 Stainless Steel at depth of feed and cooling medium. There are two independent variables and a dependent variable. The dependent variable is cutting speed 63 mm/min and feed speed 950 mm/min, while the independent variable is variation. cooling media (room air, dromus, and cooled air) and variations in feeding depth (0.5, 0.75 and 1 mm. The results obtained from this test show the influence of variations in cooling media and depth of feed on the surface roughness of Stainless Steel AISI 304. The tools and materials used are Stainless Steel AISI 304, milling machine, dromus, cold air cooler, thermometer, pressure gauge, and tools. surface roughness tester. Tests obtained the greatest roughness results in the cooling medium using room air which showed a roughness level of 0.974 μm with a cutting speed of 63 mm per min and a feed speed of 950 mm per min. Then the smallest level of roughness is in the cooling media using cold air, namely 0.296 μm with a cutting speed of 63 mm per min and a feed speed of 950 mm per min.